Xeno-free cGMP isolation and cryopreservation of clinical grade stromal vascular fraction - Frias, A. M. (2014)
Introduction In the last decades, adipose tissue (AT) has attracted attention of the scientific and industrial communities for its high therapeutic potential. When focusing on the clinical translation of such type of cells, aspects such as Good Manufacturing Practices (GMP) compliance, scalability, reproducibility, and protocol validation must be ensured. Manufacturing of cells must warrant high quality concerning cell viability, cell yield immunophenotype, and absence of any microbial or pathological contamination. This project focused on the development of a complete manufacturing and cryopreservation process of therapeutic cells for human clinical delivery, ensuring all parameters and characteristics listed above. Materials and Methods The new protocol developed is particularly compact and ensures economies of scale when increasing the volume of processed AT, which reduces manufacturing cost. In this project 100-200g AT/human donor, obtained from liposuction or lipectomy procedures (n=15) were processed under GMP conditions. Stromal vascular fraction (SVF) isolation and cryopreservation was performed using xeno-free and GMP grade reagents. Cell number and viability, before and after cryopreservation, was determined by trypan blue exclusion dye by three operators. Immunophenotype of SVF subpopulations was evaluated by flow cytometry (FACSCanto and FACSDiva software) for the expression of mesenchymal, endothelial, hematopoietic and pericytic markers: CD31, CD34, CD45, CD73, CD90, CD105, CD146 and HLA-DR. Mesenchymal trilineage differentiation was performed to demonstrate potential of the isolated cells. Results The developed xeno-free cGMP procedure for isolation of clinical grade SVF cells resulted in a cell yield of 2.4x105 ±0.9 cells/g AT, and cell viability of 85.4%±7.1, which demonstrated differentiation into mesodermal lineages. After xeno-free cryopreservation cell viability was 80.0%±10.1. Regarding immunophenotype of SVF subpopulations (Fig.1), when considering mesenchymal markers co-expressed with CD341, 12%±5 of the cells presented the CD90+CD34+CD73+CD105+ phenotype, while 1.3%±0.8 of cells expressed concomitant mesenchymal markers in the absence of CD34. Regarding endothelial markers, 15%±6 of the cells are CD45-CD34+CD31+. Preliminary analysis of samples demonstrated no significant difference of phenotypic expression before and after xeno-free cryopreservation. Discussion and Conclusions To the best of our knowledge this project is pioneer in providing clinical grade cryopreserved hSVF, ensuring extremely high viability post-thaw, and maintenance of immunophenotypic characteristics of its sub-populations. This achievement is of great relevance for therapeutic use of adipose tissue regenerative cells. References 1 Scherberich A. et al. World J Stem Cells 5, 1, 2013; 2 Bourin P. et al. Cytotherapy. 0, 1, 2013.